PEMANFAATAN PLATFORM DIGITAL UNTUK MENINGKATKAN AKTIVITAS BELAJAR PESERTA DIDIK - Budi Kurniawan; Muhamad Rusadi Letasado; Nuriyah Nuriyah; Suryadin hasyda; Nurzil Amri (Penerbit Widina, Widina Media Utama, 2026)
This study aims to analyze the improvement of students’ learning activity through the implementation of gamification-based digital platforms Blooket, Wordwall, and Puzzle.org in two elementary schools: UPTD SD Inpres RSS Oesapa (n = 22) and SD Muhammadiyah 1 Kota Kupang (n = 24). The research employed a quasi-experimental method with a one-group pretest–posttest design. Data were collected through activity observations, pretest–posttest assessments, and documentation of classroom learning processes. The effectiveness of the intervention was measured using the N-Gain Score, which evaluates cognitive improvement and learning activity enhancement. The findings indicate a significant increase in students’ learning activity in both schools. The average activity score increased by 48.18% at UPTD SD Inpres RSS Oesapa and 44.44% at SD Muhammadiyah 1. Cognitive improvement measured through the N-Gain analysis showed a moderate category, with 0.62 for UPTD SD Inpres RSS Oesapa and 0.66 for SD Muhammadiyah 1 Kota Kupang. These results confirm that gamification-based digital platforms positively impact student engagement and conceptual understanding. These findings align with Fauziyah et al. (2025), who reported that challenge-based gamification enhances enthusiasm and active participation among elementary students, as well as Amelia et al. (2025), who found that gamification significantly boosts learning motivation at the vocational school level. The mechanisms contributing to the improvements include: (1) motivational effects of gamification elements such as points, challenges, leaderboards, and instant feedback; (2) interactive visual features in Wordwall, Blooket, and Puzzle.org that support deeper conceptual understanding; and (3) the novelty effect observed in classrooms with limited prior exposure to digital learning tools. The study concludes that integrating gamification-based digital platforms is effective in enhancing learning activity, motivation, and academic performance among elementary school students. Practical implications highlight the need for teacher training, adequate digital infrastructure, and the development of continuous interactive learning designs to maximize the benefits of gamification.ABSTRAKPenelitian ini bertujuan untuk menganalisis peningkatan aktivitas belajar peserta didik melalui pemanfaatan platform digital berbasis gamifikasi, yaitu Blooket, Wordwall, dan Puzzle.org, pada dua sekolah dasar: UPTD SD Inpres RSS Oesapa (n = 22) dan SD Muhammadiyah 1 Kota Kupang (n = 24). Metode penelitian menggunakan pendekatan kuasi-eksperimental dengan desain one-group pretest–posttest. Data dikumpulkan melalui observasi aktivitas, tes awal–tes akhir, serta dokumentasi proses pembelajaran. Analisis efektivitas intervensi dilakukan menggunakan N-Gain Score untuk melihat peningkatan hasil belajar dan aktivitas. Hasil penelitian menunjukkan adanya peningkatan signifikan pada aktivitas belajar siswa di kedua sekolah. Rata-rata aktivitas siswa pada UPTD SD Inpres RSS Oesapa meningkat sebesar 48,18%, sedangkan pada SD Muhammadiyah 1 meningkat 44,44%. Analisis kognitif menggunakan N-Gain menunjukkan peningkatan kategori sedang: 0,62 untuk UPTD SD Inpres RSS Oesapa dan 0,66 untuk SD Muhammadiyah 1 Kota Kupang. Peningkatan ini menunjukkan bahwa gamifikasi digital memberikan dampak nyata terhadap keterlibatan dan pemahaman siswa. Temuan ini selaras dengan penelitian Fauziyah et al. (2025) yang membuktikan bahwa gamifikasi berbasis tantangan meningkatkan antusiasme dan partisipasi aktif siswa MI, serta studi Amelia et al. (2025) yang melaporkan bahwa gamifikasi meningkatkan motivasi belajar siswa SMK secara signifikan. Mekanisme peningkatan yang teridentifikasi mencakup: (1) efek motivasional dari elemen gamifikasi seperti poin, kompetisi, tantangan, dan umpan balik instan; (2) visual interaktif Wordwall, Blooket, dan Puzzle.org yang mempermudah pemahaman konsep; dan (3) efek kebaruan (novelty effect) pada sekolah dengan paparan teknologi rendah sebelumnya. Penelitian ini menyimpulkan bahwa integrasi platform digital berbasis gamifikasi efektif meningkatkan aktivitas, motivasi, dan hasil belajar siswa sekolah dasar. Implikasi praktis penelitian ini menekankan pentingnya pelatihan guru, penyediaan infrastruktur digital, serta pengembangan pembelajaran interaktif berkelanjutan untuk memastikan manfaat gamifikasi dapat dimaksimalkan.